Exploring Female Psychology Students’ Volunteering Experiences at the Inside-Out Outside-In South African Corrections Interest Group - Mdakane, Mbongiseni (Research in Social Sciences and Technology- OpenED Network, 2025)
In the context of higher education, as propounded by the Community Engagement and Outreach Policy (Unisa, 2013), the University of South Africa (Unisa) academics are encouraged to involve students in In-Service Learning programmes, including those who may wish to volunteer their time to gain soft skills, experiential learning, and work-related skills. This study explored the volunteerism experiences of female Psychology students as part of Unisa’s “Inside-Out Outside-In” Corrections Interest Group. An exploratory, qualitative approach grounded in a phenomenological research design was incorporated into the study, and the standard ingroup identity model was used as the study’s theoretical framework. Ten study participants were recruited purposefully, and the data were collected using semi-structured interviews and analysed thematically. The results revealed that the terrain of volunteering is abundant with learning opportunities and that the volunteering experiences are unique, vary widely across individuals, and hold different meanings to different people. The results showed that volunteering among students requires resilience as its challenges can easily lead to burnout and despondency, owing to the fluctuating emotional situations they confront in carceral communities. It was also found that upon joining the Inside-out Outside-in South African Corrections Interest Group, the students did not come ‘empty-handed’ but brought misguided perceptions about the Criminal Justice System (CJS). However, through their participation over time, they gradually developed a rational understanding of the CJS. Conclusively, this study demonstrated that volunteering manifests many benefits, including debunking personal myths about carceral communities, deriving satisfaction and a sense of purpose, and building the capacity for active citizenship.